SUFIJACIÓN Y GÉNERO GRAMATICAL - MONTERO CURIEL, Marisa; MONTERO CURIEL, Pilar (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Suffixation and Grammatical Gender. The presence in the Spanish language of words like la silla (chair) and el sillón (armchair), el lago (lake) and la laguna (lagoon), la casa (house) and el caserón (mansion) or la corbata (tie) and el corbatín (bow tie), leads us to wonder if the grammatical gender change in these pairs of non-sexed nouns is justified due to a variation in the size of the object – a type traditionally studied as a dimensional genre – or if it is imposed by the suffix that is added to the root in one of the forms, irrespective of whether or not it is a modification based on the dimensions of the object. Under this approach, we will try to address a topic which pivots on flexive morphology and derivational morphology and to which the etymology of each of the analysed forms will have a great deal to contribute in order to draw conclusive results. REZUMAT. Sufixare și gen gramatical. Prezența în limba spaniolă a unor cuvinte precum la silla (scaun) și el sillón (fotoliu), el lago (lac) și la laguna (lagună), la casa (casă) și el caserón (căsoaie) sau la corbata (cravată) y el corbatín (papion) ne face să ne întrebăm dacă modificarea genului gramatical în aceste perechi de substantive inanimate se justifică printr-o diferențiere în ceea ce privește dimensiunea obiectului -caracteristică studiată în mod tradițional ca gen dimensional- sau dacă este impus de sufixul care se adaugă rădăcinii uneia dintre forme, fără a avea în vedere dacă este vorba de o modificare bazată pe dimensiuni. Pornind de la această teză, vom încerca să abordăm o temă care se află între morfologia flexivă și cea derivativă, și pentru care etimologia fiecărei forme analizate va avea o contribuție importantă pentru a trage concluzii relevante. Cuvinte-cheie: gen gramatical, sufix, morfologie derivativă, morfologie flexivă